Effect of 3-year changes in adiposity measures on the pre-diabetes regression and progression: a community-based cohort study - Maryam Masumi; Zahra Bahadoran; Parvin Mirmiran; Davood Khalili; Farzaneh Sarvghadi; Fereidoun Azizi (BMC, 2024)
Abstract Aim We assessed the impact of a 3-year change-percent in adiposity measures on regression and pre-diabetes (Pre-DM) progression among Iranian adults. Methods Three-year change-percent in body weight (BW), body mass index (BMI), waist circumference (WC), waist-to-hip ratio (WHR), and visceral adiposity index (VAI) were calculated for 1458 Pre-DM subjects (mean age of 53.0 ± 13.7, 46.8% men), participated in the third examination of the Tehran Lipid and Glucose Study (2006-2008). Multinomial logistic regression models were used to estimate relative risk ratios (RRRs) of the outcomes [i.e., regression to normal glucose regulation (NGR), persistence in Pre-DM, and progression to newly diagnosed type 2 diabetes (T2D)] across 3-year change categories of adiposity measures (i.e., ≥ 5% decrease, 0-5% decrease, increase). Results Over nine years of follow-up, 37.7 and 39.0% returned to NGR and progressed to T2D, respectively. Decreased BW (0-5 and ≥ 5%) was associated with regression to NGR (RRRs = 1.44, 95% CIs = 1.05-1.98, and 2.64, 1.63-4.28, respectively). Decreased BMI and WC ≥ 5% were also associated with regression to NGR (RRRs = 1.63, 95% CI = 1.01-2.64; 1.69, 1.20-2.37, respectively). Changes in WHR and VAI were not associated with Pre-DM regression or progression. Pre-DM subjects with ≥ 5% BW loss had a constant FSG level overtime and a lower overall mean of FSG (116 vs. 111 and 112 mg/dL, P = 0.023 and 0.009, respectively) and 2 h-SG (154 vs. 165 and 168 mg/dL) compared to those had 0-5% BW loss or BW gain. Conclusion Short-term management of adiposity measures increases the regression probability to NGR. Targeting BW loss seems a more potent predictor of Pre-DM reversion among the adiposity measures.